The scientific heritage of Uzbekistan anthropologists and their contribution to the development of science - Sulaymanov, Amaliddin Nurboyevich (The Lingua Spectrum, 2026)
This article analyzes the formation of the science of anthropology in Uzbekistan, the stages of its development, and the scientific activities of Uzbek anthropologists in this process. The study highlights the institutional formation of anthropology in the region since the beginning of the 20th century, the emergence of scientific schools, and their significance in studying the ethnogenesis and anthropological composition of the peoples of Central Asia. In particular, the scientific research of L.V. Oshanin, one of the founders of anthropology in Uzbekistan, and representatives of his scientific school - Q.N. Najimov, T.P. Kiyatkina, B.Kh. Karmisheva, O.A. Sukhareva, T.K. Khodzhayev and other scientists - is analyzed. It is argued that the anthropological expeditions, craniological and paleoanthropological studies conducted by these scientists, as well as scientific work on the anthropological composition and ethnic history of the peoples of Central Asia, made a significant contribution to the development of regional anthropology. The article also shows the formation of anthropology as a scientific school in Uzbekistan, the traditions of the teacher-student relationship, and the important role of the scientific heritage of these scientists in the development of modern scientific research. The results of the research serve as an important scientific source in studying the anthropological characteristics and ethnogenesis processes of the peoples of Uzbekistan and Central Asia.